Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berorientasi Keterampilan Abad 21 Pada Materi Jaringan Hewan Untuk SMA - Haniza Sara; Lufri Lufri; Helendra Helendra; Ganda Hijrah Selaras (STKIP ROKANIA, 2022)
The 2013 curriculum requires students to have 21st century skills known as 4C (critical thinking, creativity, communication, and collaboration). For this reason, teaching materials are needed that are in accordance with the demands of the 2013 curriculum such as Student Activity Sheets (LKPD). This study aims to create a 21st century skill-oriented Student Activity Sheet (LKPD) on animal tissue material for high school. This type of research is research and development research and development (R & D) to produce valid and practical LKPD. The subjects of this study were 36 students of class XI SMA N 2 Tebo Regency as well as two lecturers and two biology teachers as validators. The results showed that the object of this research was the Student Activity Sheet (LKPD) oriented to 21st century skills on animal tissue material for high school. Overall obtained an average of 90.9% with very valid criteria. And the average practicality test by teachers is 95.4% with very practical criteria and by students it has an average of 93% with very practical criteria. This shows that the 21st century skill-oriented worksheets can be used in the learning process. The implications of this research are expected to be used in the learning process.